2011
DOI: 10.1186/1475-2891-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Use of a food frequency questionnaire to assess diets of Jamaican adults: validation and correlation with biomarkers

Abstract: BackgroundAssessment of habitual diet is important in investigations of diet-disease relationships. Many epidemiological studies use the food frequency questionnaire (FFQ) to evaluate dietary intakes but few studies validate the instrument against biological markers. The aim of this study was to assess the validity and reproducibility of a previously validated 70-item food frequency questionnaire (FFQ) that was expanded to 120-items to assess diet - cancer relations.MethodsRelative validity of the FFQ was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
50
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 39 publications
19
50
5
Order By: Relevance
“…Correlation coefficients comparing 24 h recalls and the FFQ ranged from 0?18 to 0?58. Correlation coefficients were comparable to those observed in other validation studies (14)(15)(16)19,20) . Nutrient data are often adjusted for energy to eliminate confounding due to energy intake and further reduces bias due to low energy reporting (3) .…”
Section: Validitysupporting
confidence: 88%
See 1 more Smart Citation
“…Correlation coefficients comparing 24 h recalls and the FFQ ranged from 0?18 to 0?58. Correlation coefficients were comparable to those observed in other validation studies (14)(15)(16)19,20) . Nutrient data are often adjusted for energy to eliminate confounding due to energy intake and further reduces bias due to low energy reporting (3) .…”
Section: Validitysupporting
confidence: 88%
“…Misclassification was higher for vitamin E, Ca, Fe, retinol and b-carotene. In general, agreement between the FFQ and the reference method was good and was comparable to that in other studies (14,15,18) . The k w statistic was used to evaluate the level of agreement and k w values above 0?4 are valid for conclusions (24) .…”
Section: Validitysupporting
confidence: 85%
“…Limits of agreement equal to 50 and 200% indicate that 95% of all participants' Paper-Web-DR estimates were between half and 2 times that of their Web-DR estimates. In addition, limits of agreement from our study were narrower than those reported by Ambrosini et al [32] and MacIntyre et al [33] but wider than those reported by Jackson et al [34]. However, we think that the limits of agreement from our study are clinically acceptable and that the developed Web-DR could be applied in a larger study.…”
Section: Discussioncontrasting
confidence: 52%
“…Dietary intakes were assessed using a previously validated food frequency questionnaire (FFQ) [16] that was expanded to assess diet and cancer in the Jamaican population [17]. In addition to frequency of consumption for each food item, subjects were asked to estimate the portion size usually consumed by using food models, commonly used household utensils, measuring cups and a measuring tape.…”
Section: Dietary Assessmentmentioning
confidence: 99%